Konservasi lahan pertanian berbasis kearifan lokal masyarakat di Desa Serang Kabupaten Purbalingga - Mahal Nungki Enggar Triastoningtias (Graduate School Bogor Agricultural University (SPs IPB), 2021)
Encroachment of forest areas can cause many problems when the management does not pay attention to conservation rules. Forest encroachment is increasingly widespread and is of particular concern to theSerang Village Government, thus encouraging agricultural systems based on local wisdom owned by the community. The study is able to record known land conservation practice, among others, (1) pranoto mongso; (2) nyabuk gunung; (3) sacralize water sources (Festival Tuk Sikopyah); (4) resting agricultural land; (5) using traditional agricultural tools; and (6) Agroforestry. The highest conservation practice is using traditional agricultural equipment by 99%, nyabuk gunung and forecasting water sources by 96%. While conservation practices are rarely carried out, namely 61% of agricultural land. Agriculture in Serang Village can be developed because it has large land resources and large market demand. Suitable agricultural land conservation strategies are implemented in the management of sustainable agricultural land in Serang Village, namely (1) preserving local wisdom owned by the community and applied in agricultural land management activities; (2) utilizing assistance from the village, district, and central governments to manage and increase agricultural production; (3) increase market distribution and utilize access to transportation; (4) increase cultivation land with available land for increased agricultural production; (5) maintain product quality and create customer satisfaction; and (6) cooperation with the distribution channel to expand the market.